Odpowiedź :
A)
3x + 6 = 21
3x = 21 - 6
3x = 15. /:3
x = 5
B)
2x + 3 = 4x - 2
2x - 4x = -5
2x = 5. /:2
x = 2,5
C)
x - 3 = 2 - 2x
-3 - 2 = - 2x - x
-5 = -3x
3x = 5. /:3
x = 5/3 = 1 2/3
D)
-3 (x + 1) = 3
-3x - 3 = 3
-3x = 6. /:(-3)
x = -2
E)
2x - 6 = 3x + 3
-x = 9
x = -9
F)
3x - 6 = 8x + 2 - 3
3x - 8x = 5
-5x = 5. /:(-5)
x = -1
3x + 6 = 21
3x = 21 - 6
3x = 15. /:3
x = 5
B)
2x + 3 = 4x - 2
2x - 4x = -5
2x = 5. /:2
x = 2,5
C)
x - 3 = 2 - 2x
-3 - 2 = - 2x - x
-5 = -3x
3x = 5. /:3
x = 5/3 = 1 2/3
D)
-3 (x + 1) = 3
-3x - 3 = 3
-3x = 6. /:(-3)
x = -2
E)
2x - 6 = 3x + 3
-x = 9
x = -9
F)
3x - 6 = 8x + 2 - 3
3x - 8x = 5
-5x = 5. /:(-5)
x = -1
Odpowiedź:
a) 3x=15 x=5
b) 5=2x x=5/2
c) 3x=5 x=5/3
d) x+1=-1 x=-2
e) 2x-3x=6+3 x=-9
f) 3x-8x=2-3+6 x=-1